Macaque Gaze Responses to the Primatar: A Virtual Macaque Head for Social Cognition Research - Wilson, Vanessa A. D.; Kade, Carolin; Moeller, Sebastian; Treue, Stefan; Kagan, Igor; Fischer, Julia (Frontiers in Psychology, 2020)
Following the expanding use and applications of virtual reality in everyday life, realistic virtual stimuli are of increasing interest in cognitive studies. They allow for control of features such as gaze, expression, appearance and movement, which may help to overcome limitations of using photographs or video recordings to study social responses. In using virtual stimuli however, one must be careful to avoid the uncanny valley effect - where realistic stimuli can be perceived as eerie, and induce an aversion response. At the same time, it is important to establish whether responses to virtual stimuli mirror responses to depictions of a real conspecific. In the current study, we describe the development of a new virtual monkey head with realistic facial features for experiments with nonhuman primates, the ‘Primatar’. As a first step towards validation, we assessed how monkeys respond to facial images of a prototype of this Primatar compared to images of real monkeys, and an unrealistic model. We also compared gaze responses between original images and scrambled as well as obfuscated versions of these images. We measured looking time to images in six freely moving long-tailed macaques (Macaca fascicularis) and gaze exploration behaviour in three rhesus macaques (Macaca mulatta). Both groups showed more signs of overt attention to original images than scrambled or obfuscated images. In addition, we found no evidence for an uncanny valley effect, since for both groups, looking times did not differ between real, realistic or unrealistic images. These results provide important data for further development of our Primatar for use in social cognition studies, and more generally for cognitive research with virtual stimuli in nonhuman primates. Future research on the absence of an uncanny valley effect in macaques is needed, to elucidate the roots of this mechanism in humans.